2015
DOI: 10.1074/jbc.m115.651042
|View full text |Cite
|
Sign up to set email alerts
|

CUX2 Protein Functions as an Accessory Factor in the Repair of Oxidative DNA Damage

Abstract: Background: CUX2 contains three Cut repeat domains and is expressed in postmitotic neurons. Results: Cut repeats stimulate the OGG1 DNA glycosylase, and lower or higher CUX2 expression, respectively, delays or accelerates repair of oxidative DNA damage. Conclusion: CUX2 functions as an accessory factor in base excision repair. Significance: CUX2 contributes to the maintenance of genome integrity in long lived neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 88 publications
0
43
0
Order By: Relevance
“…In a previous study of the CUX2 protein, we showed that the ability of a CUT domain to stimulate OGG1 was reduced following the introduction of two point mutations replacing glutamic acids to alanines [54]. In the present study, we have engineered the same point mutations with the CUT domain 1 of CUX1 (Figure 6A: C1-2Ala).…”
Section: Resultsmentioning
confidence: 83%
“…In a previous study of the CUX2 protein, we showed that the ability of a CUT domain to stimulate OGG1 was reduced following the introduction of two point mutations replacing glutamic acids to alanines [54]. In the present study, we have engineered the same point mutations with the CUT domain 1 of CUX1 (Figure 6A: C1-2Ala).…”
Section: Resultsmentioning
confidence: 83%
“…Moreover, the risk C allele of rs6490061 was associated with a higher CUX2 mRNA expression ( P = 0.0153, Figure C). Because CUX2 functions as an accessory factor that promotes the repair of oxidative DNA damage, H. pylori infection might suppress CUX2 expression and subsequently increase gastric cancer risk by damaging the DNA repair pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Because CUX2 functions as an accessory factor that promotes the repair of oxidative DNA damage, 42 H. pylori infection might suppress CUX2 expression and subsequently increase gastric cancer risk by damaging the DNA repair pathway. The cluster of DEFB family genes is located on 20q11.21 ( Figure 2).…”
mentioning
confidence: 99%
“…CAND2 gene encodes a TATA-binding protein, TIP120b, which is muscle-specific and critical for myogenesis, and the eQTL analyses also indicate that the risk allele is associated with increased expression of CAND2 [21]. Expression of CUX2 in post-mitotic neurons contributes to the maintenance of genome integrity through its stimulation of oxidative DNA damage repair [25]. Interesting, CUX2 loci were also significantly associated with ischemic stroke [21].…”
Section: Discussionmentioning
confidence: 99%